THE APPLICATION OF QUANTUM COMPUTING IN CYBERSECURITY AND DATA ENCRYPTION - Loso Judijanto (Penelitian dan Pengembangan Ilmu, 2025)
The development of quantum computing poses serious challenges to cyber security, especially in data encryption based on classical algorithms such as RSA and ECC. This research analyzes the impact of quantum computing on cybersecurity and identifies mitigation solutions such as Post-Quantum Cryptography (PQC) and Quantum Key Distribution (QKD). Using a Systematic Literature Review (SLR) approach based on the PRISMA method, this research examines literature from databases such as Scopus, Web of Science and IEEE Xplore. Analysis shows that quantum algorithms, especially Shor's Algorithm, can break asymmetric encryption efficiently, thereby encouraging the development of PQC and QKD. However, there are gaps in the practical implementation of these solutions that need to be further investigated. The research results emphasize the urgency of transitioning to encryption systems that are resistant to quantum threats, especially for critical sectors. These findings contribute to the development of cybersecurity theory and practice, while encouraging collaboration between academics, practitioners and policymakers to accelerate the adoption of stronger security systems.